AN ANALYSIS OF COMMAND SPEECH ACT IN SURAH YA-SEEN BY SAHEEH INTERNATIONAL - Susanto (STKIP PGRI Trenggalek, 2018)
Speech act is known as an action perfomed via utterances. Speech act have many little part inside and has many brances. One of them is command speech acts which is the important things in communication. Without command it will make some of conversation more ambiguous. Command speech act can find in everywhere, it also can find in Al-Quran. Because in Al-Qur’an there are many command from Allah to All of Muslims in the world. The researcher find the letter in Al-Qur’an are has many command inside is Surah Ya-seen.In this research the researcher aims is to know the types of command speech act in Surah Ya-seen by Saheeh International and the dominant form of command speech act in Surah Ya-seen by Saheeh International.In collecting the data the researcher use descriptive qualitative research exacly document analysis,because in this research the researcher conduct the written material. The subject of this research is the script of Surah Ya-seen. It use documentation as a data collection method because it is use the script of Surah Ya-seen. It also use table analysis and formula in order to achieve the objective of the research.The result of the research is the researcher find there are just one types of command speech act in Surah Ya-seen and it is direct command. The other types of command speech act is not in Surah Ya-seen is indirect. Meanwhile, the dominant form of command speech act is declarative which gain high frequency of occurance. This research is expected useful for the other researcher who are conduct the similar study. The researcher expected if all of Muslims realize there are many command in al Qur’an from Allah to them. Because through this research the researcher present some of messages are Allah deliver for Muslims in Surah Ya-seen.